2012
DOI: 10.1021/nl303161d
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Tailored Dielectric-to-Metal Transition for the Design of Metamaterials from Nanoimprinted Colloidal Nanocrystals

Abstract: We demonstrate optical metamaterial design using colloidal gold nanocrystal building blocks. In the solid state, chemically exchanging the nanocrystals' surface-capping molecules provides a tailorable dielectric-to-metal transition exhibiting a 10(10) range in DC conductivity and dielectric permittivity ranging from everywhere positive to everywhere negative throughout the visible-to-near-IR. Direct, wide-area nanoimprinting of subwavelength superstructures at room temperature, on plastic and glass substrates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
170
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(177 citation statements)
references
References 50 publications
6
170
1
Order By: Relevance
“…Moreover, superlattices with higher metal volume fractions exhibit rich optical behavior (8)(9)(10)35). It is likely that the strong, nonlinear plasmonic coupling in these systems will increase the effect of randomness, disorder, and polydispersity on the optical response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, superlattices with higher metal volume fractions exhibit rich optical behavior (8)(9)(10)35). It is likely that the strong, nonlinear plasmonic coupling in these systems will increase the effect of randomness, disorder, and polydispersity on the optical response.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that further investigation of closely coupled plasmonic lattices will uncover unexpected and unusual plasmonic behavior (35). For example, numerous studies of closely coupled plasmonic nanoparticles have identified tunable reflection and dielectric behavior in addition to unique symmetrydependent properties (5,(8)(9)(10)13). These insights will lead to materials and devices that exhibit greater reproducibility including sensing, metamaterials, coatings, and optical electronics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has shown previously that compact ligand exchange increases the coupling between Au NCs, inducing an insulator-to-metal transition in Au NC thin films. 33 Figure 1 (e) shows a representative scanning electron micrograph (SEM) of a Au NCbased nanorod array [Supporting Information Figure S1]. SEM images are taken from different regions of the sample to determine the uniformity in the nanorod dimensions across the array [Supporting Information Figure S2].…”
mentioning
confidence: 99%
“…33 Since we fabricate anisotropic nanostructures as building blocks for metasurfaces, we probe their polarization control of incident light. The polarization-dependent transmittance spectra for the four samples in Figure 2 for (a) as the aspect ratio of the nanorods increases.…”
mentioning
confidence: 99%